2013
DOI: 10.1111/idh.12039
|View full text |Cite
|
Sign up to set email alerts
|

Learning experiences of oral hygiene students in the clinical environment

Abstract: The results of this study suggest that a blueprint defining assessment as a means to drive student learning is inadequate. A more comprehensive approach encompassing all the parameters that impact the learning process may be more useful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(73 reference statements)
0
5
0
1
Order By: Relevance
“…These findings are supported by Gordon who reported that the factors influencing student learning and the acquisition of competencies include a supportive environment to building clinical skills together with ‘patient appreciation and positive reinforcement from the clinical supervisors’ . This also includes the need for consistent and appropriate feedback that is timely, non‐threatening and espouses to upholding the ethical values and principles that underpin the profession .…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…These findings are supported by Gordon who reported that the factors influencing student learning and the acquisition of competencies include a supportive environment to building clinical skills together with ‘patient appreciation and positive reinforcement from the clinical supervisors’ . This also includes the need for consistent and appropriate feedback that is timely, non‐threatening and espouses to upholding the ethical values and principles that underpin the profession .…”
Section: Resultsmentioning
confidence: 78%
“…This also includes the need for consistent and appropriate feedback that is timely, non‐threatening and espouses to upholding the ethical values and principles that underpin the profession . The quality of feedback, namely inconsistencies in assessment methods, and possible subjectivity in the execution of assessments (despite the availability of set clinical tools) could create further tensions in the student–supervisor relationship and consequently threaten the student learning process .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An enabling environment is very important for active student learning. This is further supported by Gordon, [23] who confers that a supportive environment is essential in building clinical competencies in students.…”
Section: Theme 3: Support Providedmentioning
confidence: 91%